THE EFFECT OF RICE VARIETY TO ANTIMICROBIA ACTIVITY OF RED MOULD RICE BY Monascus purpureus - Martina Andriyani (Universitas Sebelas Maret, 2009)
The aim of this research is to know the antimicrobia activity of red mould rice from white rice, red rice and black rice. This research have been done at Food and Nutrient Laboratory and Manipulated of Process Laboratory, Agricultural Product Technology Department, Agriculture Faculty, Sebelas Maret University of Surakarta, started from Mey 2008 until September 2008. This research used factorial experiment that arranged in Randomized Complete Design (RCD) with 2 experimental factors. The first factor was three levels of rice variety i.e: white rice (B1), red rice (B2), black rice (B3). And second factor was fourth levels of extract concentrations i.e: 2,5% (K1), 5,0% (K2), 7,5% (K3) and 10% (K4). Obeservation variables include the total colony of Pseudomonas aeruginosa and Escherichia coli, with plate count method. Result of this research shows that the interaction of rice variety of red mould rice and the extract concentration effected to Pseudomonas aeruginosa and not affected to Escherichia coli. The extract of red mould rice from black rice with 10% concentration extract, have the highest antimicrobial activity to Pseudomonas aeruginosa. The conclutions of this reserach is rred mould rice have an antimicrobial activity. Red mould rice from black rice have an antimicrobial activity higher than red mould rice from red rice and red mould rice from white rice.